Preoperative Vaginal Preparation for Prevention of Post-Cesarean Endometritis [22L]. (May 2018) - Edinoff, Amber; Drake, Chelsea; Pile, Rachel; Sutton, Maureen; Bhattarai, Bikash; Coonrod, Dean
Abstract : INTRODUCTION: Endometritis complicates 6%–27% cesarean deliveries (CD). A recent meta-analysis showed a reduction in endometritis with vaginal cleansing prior to CD (4.5% versus 8.8%). Our study examines the proportions of endometritis from two time periods–prior to and after the implementation of vaginal preparation prior to CD at one hospital. We aim to see the effect shown in research in clinical practice. METHODS: A retrospective chart review of 356 women undergoing cesarean delivery prior to and after the policy change. After implementation of the vaginal preparation protocol, a policy of administration of 400 μg of buccal misoprostol for postpartum hemorrhage prophylaxis was instituted so this was recorded. Odds ratios (OR) and 95% confidence interval (CI) of endometritis diagnosed by ICD code or 2+ symptoms were calculated. RESULTS: The rate of endometritis was 3.8% in the pre-policy period and 15.2% post-policy, OR 4.5 (95% CI 1.7–11.8). Notably the frequency of fever was 4.5% pre-policy compared with 22.2% post-policy. When the rates of endometritis with those given misoprostol were excluded the rates were 3.8% pre-policy and 6.7% post-policy, OR 1.8 (95% CI 0.5–6.6). CONCLUSION: When comparing rates of endometritis after instituting a vaginal preparation protocol we found a paradoxical increase in the rate of endometritis. However, this could be driven by the increased rate of fevers associated with misoprostol prophylaxis. When this was accounted for, there was a non-significant increase. Confounding factors may lead to important differences from randomized studies and are important to assess when evaluating practice change.